Exploring classroom management challenges and strategies among EFL school pre-service teachers in the Kurdistan region of Iraq - Ibrahim, Mokhles Saleh; Ahmed, Nehad; Mohammed, Mohammed Hussein (Universitas Ahmad Dahlan, 2025)
This research aimed to investigate the pre-service teachers' challenges and strategies in classroom management during the school practicing process. The mixed-method research approach was implemented in the study. The data was collected through diary writing and semi-structured interviews. The study participants were six male and six female undergraduate students or pre-service teachers in the faculty of basic education at a public university in the Kurdistan Region of Iraq (KRI). In addition, eight professors from the faculty, who observed them during the process, were assigned as the interviewers. Furthermore, the data from the diary was organized by means of checklist and then analyzed by using SPSS Program. Furthermore, the data from the semi-structured interview was analyzed by using the thematic descriptive analysis method. The results of the study showed that male and female pre-service teachers have common challenges in managing their teaching classrooms effectively. However, the study found that pre-service teachers implement various strategies for dealing and addressing the classroom issues.